Antibiotics in Children with Pneumonia: a Review - Kurniasih, Fatimah Intan; Hanifah, Suci (Pharmacon: Jurnal Farmasi Indonesia, 2025)
Pneumonia is one of the most common infections in children; at the same time, it's also a case that consumes lots of days in hospitals with antibiotics. Essentially, antibiotics are medicines that specifically combat infection produced by bacteria, turning out to be some of the important discoveries in the entire history of medicine. This review aims to analyze the types of sensitive and resistant antibiotics in the management of pneumonia in children. Antibiotic resistance is one of the most dangerous health hazards facing the global community, which has grave consequences economically. The literature search in this study is adopted from both Google Scholar and PubMed. While on Pubmed, the keyword used includes "pneumonia", "antibiotics", "children", "PICU"; on Google Scholar, the word used is antibiotics, pneumonia, pediatric, and intensive care joined by using "AND" or "OR". The inclusion criteria in this literature search include published literature within less than 10 years, between 2014 and 2024; antibiotic articles on use scheme in the PICU; literatur of pneumonia in pediatric; and study review about bacterial type examinations. Thus, other articles were excluded that did not represent any empirical data regarding the study of antibiotics, or those that focused only on one kind of antibiotic sine the contextualization of its usage design. From the outcome of the review, the following bacteria types have been identified to be present in pneumonia patients: M. pneumoniae, Acinetobacter baumannii, Staphylococcus, Pseudomonas, and K. pneumoniae. Tetracycline and fluoroquinolone groups are effective choices of antibiotic classes. Mycoplasma pneumoniae, a common bacteria in pneumonia patients with CAP, is resistant to macrolides, leading to the recommendation of combination therapy or tetracycline antibiotics. Meropenem, widely used in VAP patients, is now limited and recommended for other types.